2015
DOI: 10.3390/rs70404604
|View full text |Cite
|
Sign up to set email alerts
|

Regional Leaf Area Index Retrieval Based on Remote Sensing: The Role of Radiative Transfer Model Selection

Abstract: Physically-based approaches for estimating Leaf Area Index (LAI) using remote sensing data rely on radiative transfer (RT) models. Currently, many RT models are freely available, but determining the appropriate RT model for LAI retrieval is still problematic. This study aims to evaluate the necessity of RT model selection for LAI retrieval and to propose a retrieval methodology using different RT models for different vegetation types. Both actual experimental observations and RT model simulations were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 77 publications
(102 reference statements)
0
22
0
Order By: Relevance
“…The changes in RMSE of NDVI and slope NDVI, land cover type, and slope were selected as auxiliary variables in this study. This is because they are widely used in the generation of high-resolution reference LAI map in mountainous areas based on literature research [31,32,38,39,45]. NDVI is calculated as a ratio between the red (R) and near infrared (NIR) reflectance in the form of (NIR − R)/(NIR + R), and it may be the most widely used vegetation indices in the generation of high-resolution reference LAI map.…”
Section: Sensitivity To Sample Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in RMSE of NDVI and slope NDVI, land cover type, and slope were selected as auxiliary variables in this study. This is because they are widely used in the generation of high-resolution reference LAI map in mountainous areas based on literature research [31,32,38,39,45]. NDVI is calculated as a ratio between the red (R) and near infrared (NIR) reflectance in the form of (NIR − R)/(NIR + R), and it may be the most widely used vegetation indices in the generation of high-resolution reference LAI map.…”
Section: Sensitivity To Sample Numbermentioning
confidence: 99%
“…Although the reflectance data can be used in high-resolution LAI mapping, vegetation indexes are more often used in validation activities. Commonly used vegetation indexes include normalized difference vegetation index (NDVI) [36], simple ratio (SR) [37], and reduced simple ratio (RSR) [38]. In mountainous areas, slope extracted from digital elevation model (DEM) data is often used to account for the terrain effects [31,39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To calculate r c m and r c x from r sm and r sx , maximum possible LAI is required [21]. Since the vegetation under each site is maize, a maximum possible LAI of 5.0 was selected in the Moran method [32]. FVC was calculated from NDVI using a non-linear relationship, i.e., FVC = [(NDVI − NDVI min )/(NDVI max − NDVI min )] 2 where NDVI min and NDVI max were set as 0.2 and 0.86 [19].…”
Section: Study Area and Materialsmentioning
confidence: 99%
“…This problem may be caused by the use of the PROSAIL model, which is mainly related to leaf biochemical content, but during the non-growth period, few leaves are left. Yin, Li [52] found that the canopy structure representation of the radiative transfer (RT) model has substantial implications for LAI.…”
Section: Errors Introduced By the Radiative-transfer Modelmentioning
confidence: 99%